Polymeric nanocarriers as stimuli-responsive systems for targeted tumor (cancer) therapy: Recent advances in drug delivery - Mosa Alsehli (Elsevier, 2020)
In the last decade, considerable attention has been devoted to the use of biodegradable polymeric materials as potential drug delivery carriers. However, bioavailability and drug release at the disease site remain uncontrollable even with the use of polymeric nanocarriers. To address this issue, successful methodologies have been developed to synthesize polymeric nanocarriers incorporated with regions exhibiting a response to stimuli such as redox potential, temperature, pH, and light. The resultant stimuli-responsive polymeric nanocarriers have shown tremendous promise in drug delivery applications, owing to their ability to enhance the bioavailability of drugs at the disease site. In such systems, drug release is controlled in response to specific stimuli, either exogenous or endogenous. This review reports recent advances in the design of stimuli-responsive nanocarriers for drug delivery in cancer therapy. In particular, the synthetic methodologies investigated to date to introduce different types of stimuli-responsive elements within the biomaterials are described. The sufficient understanding of these stimuli-responsive nanocarriers will allow the development of a better drug delivery system that will allow us to solve the challenges encountered in targeted cancer therapy. Keywords: Stimuli-responsive, Smart polymer, Polymeric nanocarriers, Cancer therapy, Drug delivery